Synthesis and characterization of bioactive biodegradable chitosan composite spheres with shape memory capability - Leite, Álvaro J. (2016)
Chitosan (CHT) spheres incorporating bioactive glass nanoparticles (BGNPs) were prepared to obtain a composite system able to induce the deposition of an apatite layer upon immersion in a biological-like environment. Spheres were synthesized with different concentrations of BGNPs obtained from a solâ gel route and genipin (GNP, the crosslinking agent). Biomimetic superhydrophobic surfaces were used to support droplets of chitosan-based solutions that after crosslinking enabled to produce well developed spherical particles with controlled sizes. From SEM and EDS analysis it was observed the successful formation of bone-like apatite on the surface when the spheres were immersed in a simulated body fluid (SBF). Lower GNP concentration promoted more apatite formation. The spheres presented shape memory behaviour triggered by hydration with high values of shape fixity and shape recovery. This effect was used to introduce these spheres in a bone defect showing a good geometrical accommodation in the implanted site. The bioactive spheres allowed the incorporation of a drug model and its effective release. Overall the developed nanocomposite spheres showed great potential for bone tissue engineering in particular as a device to be implanted using minimal invasive procedures.